Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2022)
A dataset containing 238289 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", "TaxonKey is Viperidae" ] } The dataset includes 238289 records from 765 constituent datasets: 4 records from Borders Backyard Biodiversity. 2 records from Comunidad de Reptiles presentes en el Cerro Jánano. 5 records from NZCS Vertebrates Old Collection Before 1987. 11 records from Inventario y monitoreo de anfibios, reptiles y mariposas en la Reserva de Calakmul, Campeche, Fase II. 24 records from Angolan Herpetological Collection - IICT. 1 records from Données espèces - Expertise IQE 89. 6 records from Reptiles de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 564 records from SEWBReC Reptiles (South East Wales). 10 records from Monitoreo de la Fauna Silvestre con Capacitación y Certificación de Monitores Comunitarios en las Microrregiones Prioritarias para la Conectividad y Conservación de la Biodiversidad Agua Blanca, Cañón del Usumacinta, Sierra de Tabasco, *. 225 records from Records of protected animal, plant and fungi species in Ukraine. 321 records from UTEP Fossils (Arctos). 137 records from Anfibios y reptiles del estado de Tamaulipas, México. 4 records from Biodiversidad asociada al gasoducto Paiva-Caracolí. 1 records from Données du/de la naturaliste LABBAYE Olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Inventaire "Espaces Naturels Sensibles" du Plata (SORE). 1 records from Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 11 records from Patrick Roper’s Notebooks. 1 records from Caracterización ecológica de la comunidad de herpetos de la ciénaga La Honda, Tanguí. 4 records from Données de la naturaliste Lucile Ferriot. 154 records from Carnet B Centre - lot 2012. 10 records from DREAL_PACA_-_N2000_-_Office_National_des_Forêts_06_2017_12_18. 21 records from Registro de Fauna Silvestre en el Inventario Nacional Forestal y de Fauna Silvestre-SERFOR, Perú. 305 records from The Danish Environmental Portal, species and habitats-database "Danmarks Miljøportals Naturdatabase". 4 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 1 records from Données du naturaliste ducourneau philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Inventario multitaxonómico (plantas, crustáceos y vertebrados) del APFF Meseta de Cacaxtla, Sinaloa, México. 1 records from Inventario Herpetológico EPF Floreña, Yopal, Casanare. 693 records from Census of the animals of Benin. 10 records from Caracterización de fauna para el establecimiento de nuevas Reservas Naturales de la Sociedad Civil en Arauca. 3 records from Transmissions de données opportunistes du Parc Naturel Régional Périgord-Limousin (PNRPL). 62 records from Herpetology Collection - Instituto Nacional de Pesquisas da Amazônia. 640 records from Amphibian and reptile data for Dumfries and Galloway.. 84 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (MZFC_HE). 3 records from Monitoreo y seguimiento de fauna terrestre para el AID y AII de la Central Hidráulica de Calima. 2018. 1041 records from Puntos de presencia en Baja California (Herps). 13 records from DREAL_PACA_-_N2000_-_Commune_de_Névache_2017_12_18. 3 records from Observations naturalistes et collection entomologique en Guyane (SEAG, Julien Touroult). 11 records from VERTEBRADOS DE VALOR ESPECIAL EN ÁREAS PROTEGIDAS DE LA ARGENTINA. 4 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 11 records from Actualización de la taxonomía y distribución de los anfibios y reptiles de San Luis Potosí. 1 records from Análisis ecológico de la fauna en las fuentes abastecedoras de agua para comunidades indígenas de Osbezcac en la cuenca del rio Saija, Timbiquí - Cauca. 307 records from India Biodiversity Portal publication grade dataset. 115 records from La Colección Herpetológica de la Estación de Biología Tropical Los Tuxtlas, Veracruz. 6 records from Données du naturaliste Pierre Rivallin provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Animals of Ukrainian Slobozhanshchina and Polissia. 125 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 1 records from Données du/de la naturaliste FAUCHER Alexandre provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from NZCS Tafelberg Expeditions 2003/2005/2013. 2 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 3705 records from CAS Herpetology (HERP). 775 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe). 4 records from Área ocupada por especies de fauna en el Parque Nacional Natural Selva de Florencia en el 2018. 20 records from Inventario multitaxonómico del ANP Médanos de Samalayuca. 2 records from PROSERPINE_2017_12_18. 252 records from Carnet B Lorraine. 42 records from DREAL_PACA_-_N2000_-_Parc_National_des_Ecrins_2017_12_18. 1 records from Caracterización biológica de la ventana de biodiversidad municipio de Filandia, Quindío, Colombia. 8 records from SUI Vertebrate Collection. 17 records from Forêt régionale de Grosbois - suivi écologique 2007-2013. 1 records from Données du naturaliste Thibedore Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Données naturalistes de GAULTIER Cyrille. 102 records from Regroupement de données amphibiens et reptiles récoltées sur la période de 1983-2014 par Cistude Nature. 91 records from Bosque Mesófilo de Montaña de México. 5 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 3212 records from Museum of Comparative Zoology, Harvard University. 1 records from Annales de la Société Linnéenne de Maine-et-Loire. 33 records from Herpetology Collection NRM. 4 records from Species found in the NOMS estate 2005 - Present. 125 records from Conservación de serpientes de cascabel de la península e islas del Golfo de California y del Pacífico. 4 records from Diversidad biológica y conservación del ecosistema de los perros de la pradera (Cymomys ludovicianus). 21 records from Données naturalistes de CERCOPE (Jean-Louis PRATZ). 1 records from Tejidos colectados en la serranía de las Quinchas, Boyacá - Proyecto Boyacá BIO. 486 records from University of Florida Vertebrate Paleontology. 14 records from Données de la structure ANVL (Association des Naturalistes de la Vallée du Loing et du Massif de Fontainebleau) provenant de la base de donnée du SINP Île-de-France CETTIA. 56 records from Données de la structure Naturessonne provenant de la base de donnée du SINP Île-de-France CETTIA. 10 records from Computarización de las Colecciones de Anfibios y Reptiles del Centro de Investigaciones Biológicas de la Universidad Autónoma del Estado de Hidalgo. 2444 records from The Taiwan Roadkill Observation Network Data Set.. 7 records from SER Site-based Surveys. 2 records from Données naturalistes de Monsieur VILAIN Frederic. 3 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2009. 3 records from Reptiles presentes en la colección herpetológica SINCHI de la expedición al Río Apaporis - Proyecto Colombia BIO. 1 records from Quarrendorfer Landschaftsschutzgebiet. 109 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 7 records from Observations Regelink Ecology and Landscape. 1 records from Rwanda's wetlands biodiversity data from different inventories that were conducted between year 2008 and 2017. 12 records from Données naturalistes de Françoise SERRE-COLLET. 39 records from Formación de una base de datos y elaboración de un atlas de la herpetofauna de México (Anfibiosreptiles_catálogo). 29 records from Amphibian and reptile species occurrences in the Tana River Basin, Kenya, digitized from preserved specimens at the National Museums of Kenya. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 126 records from Steinhardt Museum of Natural History (SMNHTAU) Vertebrates. 4 records from Données de la naturaliste Marion Laprun-Parisot. 9 records from Données du/de la naturaliste Vidal Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 200 records from Données faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 1 records from Parc_Naturel_Régional_des_Préalpes_d'Azur_2017_12_18. 6 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 1 records from Inventaire des reptiles 2014. 1 records from University of Tartu Natural History Museum and Botanical Garden Zooloogical Collections. 378 records from Universidad del Valle de Guatemala - Colecciones Biológicas - Reptiles. 1 records from Données du/de la naturaliste Mallard stephane provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Données du/de la naturaliste delzons olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Données naturalistes de la Société pour le Muséum d'Orléans et les Sciences (SOMOS). 11 records from Données naturalistes de Damien AVRIL. 273 records from INSDC Sequences. 7 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 3 records from Anfibios y reptiles del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 47 records from Leicestershire and Rutland Environmental Records Centre records 2000-2009. 151 records from PSM Vertebrates Collection. 1 records from Jeu de données convention CD78-Service du patrimoine naturel-2014-2015. 26 records from National Finnish butterfly monitoring scheme (NAFI) (NAFI). 1232 records from TNHC Herpetology Collection. 1 records from A new pit viper of the genus Trimeresurus (Lacépède, 1804) (Squamata: Viperidae) from Southwest China. 2 records from Herpetos del cerro Iró, municipio del río Iró, Chocó. 2020. 7 records from Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 120 records from ONF_2017_12_18. 65 records from Macaulay Library Audio and Video Collection. 3 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 2 records from Museu Darder de Banyoles. 4 records from Tejidos colectados en la expedición al municipio Cimitarra, Santander - Proyecto Santander BIO. 2 records from Guinea-Bissau Herpetological Collection - IICT. 2 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 1996 records from NCSM Herpetology Collection. 6 records from NBMB Herps. 96 records from BioFokus. 10 records from Arizona State University Vertebrate Tissue Collection. 3 records from Anymals+plants - Citizen Science Data. 32 records from Données de la structure Département 91 provenant de la base de donnée du SINP Île-de-France CETTIA. 246 records from ZUEC-REP - Coleção de Répteis do Museu de Zoologia da UNICAMP. 256 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 1 records from Etude d'incidence Natura 2000 travaux talus ferroviaire commanditée par SNCF réseau. 71 records from Amphibians and Reptiles census in the Western Siberia (2010-2020 years of research). 1 records from Données de la structure Ville de Paris provenant de la base de donnée du SINP Île-de-France CETTIA. 21 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 1 records from Herpetofauna, avifauna y plantas de Puerto Salgar, Caparrapí, Guaduas y Quebradanegra (Cundinamarca). 136 records from Données du/de la naturaliste CARON Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Biodiversidad asociada al proyecto de aprovechamiento de recursos minerales Queresas y Porvenir en el municipio de Planeta Rica. 2 records from Caracterización faunística de la Reserva Forestal Protectora Regional Brisas del Rincón. 2 records from Caracterización de Reptiles del corredor biológico Cértegui - Yerrecuí - Amurrupá. Sector Amurrupá. 146 records from Atlas of the Amphibians and Reptiles of Poland. 20 records from UMNH Reptiles and Amphibians Collection (Arctos). 1 records from Données du/de la naturaliste Mercier Antoine provenant de la base de donnée du SINP Île-de-France CETTIA. 619 records from Atlas of Amphibians and Reptiles of Portugal. 167 records from International Barcode of Life project (iBOL). 104 records from Amphibians and Reptiles collection at the Natural History Museum of Denmark (SNM). 1 records from Gaïadomo_2017_12_18. 16 records from Inventario de la biodiversidad de vertebrados terrestres de los Chimalapas, Oaxaca. 2 records from A new species of green pit vipers of the genus Trimeresurus Lacepede, 1804 (Reptilia, Serpentes, Viperidae) from western Arunachal Pradesh, India. 129 records from BRERC species records from all years at full resolution excluding Notable Species within the last 10 years. 788 records from Reptilia notes, NTNU University Museum. 13 records from National Wetland Inventory (NV). 5 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 1 records from Biodiversidad asociada al proyecto Parque Solar Fotovoltaico Tepuy. 4 records from Inventario de Fauna Vertebrada de la Reserva Forestal Protectora Regional de los Cañones de los Ríos Melcocho y Santo Domingo. 2222 records from Hatikka.fi observations. 2 records from Caracterización biológica de la ventana de biodiversidad Ciénaga, Municipio de Ciénaga, Magdalena, Colombia. 499 records from Données du parc national de la Vanoise. 1 records from Données naturalistes de Paul ROUVEYROL. 1 records from Données de la structure Département 78 provenant de la base de donnée du SINP Île-de-France CETTIA. 75 records from Données naturalistes faune du Conservatoire des espaces naturels Auvergne saisies avant le 18 février 2019.. 56 records from List of animalia, fungi and plant species recorded through naturalist observations and research activities in Benin. Data mobilized in the framework of a JRS Biodiversity Foundation project of Benin. 12 records from Inventario herpetofaunístico del valle semiárido de Tehuacán-Cuicatlán (continuación). 8 records from Données du/de la naturaliste Vanhille françois provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Anfibios y reptiles de la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 33 records from Application INPN Espèces: Observations naturalistes, participatives et opportunistes, fondées sur des photographies. 381 records from Biodiversity Now / Nature Check (Biodiversitet Nu / NaturTjek). 2 records from Biodiversidad asociada al Estudio de Impacto Ambiental del campo de producción Cumanday. 21 records from inatura - Erlebnis Naturschau Dornbirn. 3 records from Species Records for John Muir Trust Properties 2007-2009. 1097 records from Données d'occurrences Espèces issues de l'inventaire des ZNIEFF. 1 records from Anfibios y reptiles de la expedición en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 1 records from Classic localities of endemic amphibians, reptiles and mammals from the Western Balkans. 222 records from Löydös Open Finnish Observation Database. 1 records from Images and observations of mostly edible plants in Stephen Barstow’s Edible Garden in Norway, taken between 2005 and 2014. 38 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 340 records from North East Scotland Amphibians & Reptiles 1850 - 2016. 3 records from La Planète Revisitée, massif du Mitaraka, mission principale (février-mars 2015). 46 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 1 records from Shire Group IDB species data 2004 to present. 16 records from RNF - Données du Conservatoire d'espaces naturel Limousin. 21 records from RNF - Données de l'Association GEREPI (GEstion de la REserve naturelle nationale du PInail). 1 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 1 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 1 records from Données du/de la naturaliste BITSCH Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 148 records from Observations occasionnelles Parc national des Pyrénées. 2510 records from MSB Amphibian and Reptile Collection (Arctos). 2 records from Zielbach (Töll). 1 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 2575 records from Amphibiens et Reptiles de France métropolitaine (Enquête 1). 5 records from Type specimens of reptiles in BNHS. 6 records from Inventario herpetofaunístico de la reserva de la biosfera La Sepultura, Chiapas, México. 2983 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 5 records from Wildwatch North Pennines AONB project records for Cumbria. 1 records from Biological diversity of Kaniv (Cherkasy region) and Rzhyshchiv city amalgamated territorieal community (CATC) (Kyiv region).. 5 records from Inventario de especies de vertebrados para apoyar la creación del Ordenamiento Ecológico y la Reserva de la Biósfera Janos, Chihuahua. 23 records from Données de la structure Seine-et-Marne Environnement provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Chronicle of Nature - Phenology of Reptiles of National Park Bashkirija. 2 records from Bernice P. Bishop Museum. 2389 records from LACM Vertebrate Collection. 7 records from Inventario herpetofaunístico del noroeste de Hidalgo. 1 records from Données du naturaliste PROVOST romain provenant de la base de donnée du SINP Île-de-France CETTIA. 40 records from Amphibian and reptile records for Great Britain 2016-2019. 7 records from Données du/de la naturaliste HEUCLIN Daniel provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 18 records from Diversidad de grupos selectos de vertebrados (Reptilia, Amphibia) e insectos (Lepidoptera: Papilionoidea y Hesperioidea; Odonata; Diptera: Bombyliidae) en el Valle de Cuatrociénegas y Sierra de la Madera, Coahuila, México. 15 records from WTSWW Data: All Taxa (West Wales). 1 records from Données espèces - Expertise IQE 88. 68 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 10 records from RNF - Données de l'association Nature Nord Isère LO PARVI. 1 records from Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 187 records from BYU Herpetology Collection. 1 records from amphibians_reptiles_bsnp_peru. 25 records from Colección de reptiles del Museo de Historia Natural, Universidad de Caldas. 42 records from Base de datos de la colección herpetológica de la Facultad de Ciencias de la Universidad Autónoma de Baja California. 1 records from A new karst-dwelling, colorful pitviper (Viperidae: Trimeresurus) from northern Peninsular Thailand. 10 records from Reptile specimens of Yamagata Prefectural Museum. 25 records from Données de l'ONF provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Dorset Sites of Nature Conservation Interest (SNCI) species records 2000-2008. 2609 records from DOF - Observations from the Danish Ornithological Society. 83 records from An Extended dataset of registration points of species listed in Resolution 6 and 4 of the Bern Convention. 454 records from Observatoire LPO Franche-Comté des espèces (oiseaux, amphibiens, reptiles, mammifères sauf chauve-souris). 6 records from CPERC Combined Dataset. 521 records from HBRG Vertebrates (not Badger) Dataset. 2 records from Données naturalistes de Monsieur CSUTOROS Antoine. 143 records from Gloucestershire Historic Wildlife Sightings prior to 1st Jan 2000. 6 records from Royal BC Museum - Herpetology Collection. 2 records from Modernisation des ZNIEFF du PnrL. 3 records from National Museum of Natural Science. 1 records from Données de mortalité de la faune par collision avec les véhicules sur le réseau routier de la DIR Ouest. 1441 records from Observations faune et flore du Parc national des Écrins. 68 records from DIBA-Parc Natural del Montseny. 1 records from Inventaire et regroupement de données Natura 2000. 1 records from Données de la naturaliste Laurence Beauchamp. 269 records from Colección de Herpetología del Instituto de Ciencias Naturales (ICN-MHN-Her). 1 records from Collection contest. 1 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 43 records from Inventario herpetofaunístico del valle semiárido de Tehuacán-Cuicatlán. 1 records from Selected observations from various biodiversity surveys in Aguada Pichana Este & San Roque South Blocks between 2019 & 2021 - Total Austral. 1 records from Données naturalistes de MICHALKE Friedrich. 8 records from Enregistrement de la faune sauvage hébergée au centre de sauvegarde du CHENE en Haute-Normandie. 1358 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 73 records from Estonian Naturalists’ Society. 1 records from Données de la structure Fédération 77 de Pêche et Protection du Milieu aquatique provenant de la base de donnée du SINP Île-de-France CETTIA. 1730 records from CEN_PACA_2017_12_18. 4 records from Inventario nacional de especies vegetales y animales de uso artesanal. 5 records from Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Asian Herpetological Collection - IICT. 5 records from Kenya Virtual Museum Records. 773 records from Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2018.. 32 records from All taxa records for Leicestershire and Rutland. 757 records from Anfibios y reptiles de las regiones 30 (Parque Natural Sierra Maderas del Carmen); 31 (Sierra El Burro-Río San Rodrigo); 36 (Sierra La Encantada); y 37 (Sierra El Pino), Coahuila. 53 records from Some finds of amphibians and reptiles in Kharkiv region, Ukraine. 1007 records from Parc_National_des_Ecrins_2017_12_18. 53 records from RNF - Données du Parc Naturel Régional du Vercors. 25 records from Natural History Museum Rotterdam - Specimens. 3 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 99 records from CarNET B - Lot 2013. 3 records from Données naturalistes d'Anne TINCHANT. 4 records from AGRESTIS_2017_12_18. 461 records from AUMNH Herpetology Voucher Collection. 7 records from Chronicle of Nature - Phenology of Reptiles of Kondinskie Lakes National Park named after L. F. Stashkevich. 18 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 18 records from Proyecto COL88611 para la conservación y uso sostenible de ecosistemas secos. 5 records from Reptiles y anfibios registrados en las cuencas bajas del Guayabero, Duda y Losada, Meta. 281 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 60 records from Vertebrats d'Andorra. 2 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 1 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 6 records from Jeux de données provenant de l'ATBI Mercantour. 1 records from Biodiversidad de un bosque seco tropical del Valle Medio del río Magdalena: evaluación integrada a través de multitaxones. 2 records from Reptiles y aves del Distrito Nacional de Manejo Integrado Cabo Manglares Bajo Mira y Frontera, Pacífico colombiano - Proyecto Colombia BIO. 11 records from Herpetofauna de la reserva de la biósfera Valle de Tehuacán-Cuicatlán (etapa final). 159 records from BioGIS - Reptiles - INPA database. 89 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 43 records from Données naturalistes de Patrick HAFFNER. 1 records from Biodiversity Survey of Echuya forest, Year 2012. 260 records from Leicestershire and Rutland Protected and Conservation Priority/BAP Specie. 10 records from NHMO DNA Bank Fish and Herptile collection. 1956 records from KUBI Herpetology Collection. 2 records from Herpetofauna del Alto del Buey, Bahía Solano, Chocó. 13 records from DREAL_PACA_-_N2000_-_Office_National_des_Forêts_05_2017_12_18. 21 records from DREAL Auvergne - Reptiles - 2015. 64 records from SMNS Herpetologie. 62 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 6 records from Leicestershire and Rutland Environmental Records Centre records 2015-2019. 6744 records from Artportalen (Swedish Species Observation System). 3 records from Tejidos colectados en la expedición al municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 4 records from Données naturalistes de Julien ROUSSEAU. 3749 records from Norwegian Species Observation Service. 1 records from PlutoF platform reference-based occurrences. 13 records from Mozambique Herpetological Collection - IICT. 182 records from UAZ Herpetology Collection. 131 records from Données des réserves naturelles nationales gérées par la Ligue pour la protection des oiseaux (LPO). 266 records from Tissues Specimens. 5 records from Monitoreo de Flora y Fauna de los Acuerdos de Conservación Voluntaria como estrategia de inversión del 1% de Equión Energía Limited. 7 records from Environment Agency Rare and Protected Species Records. 1 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 149 records from DREAL_PACA_-_N2000_-_CEN_PACA_2017_12_18. 29 records from Herpetofauna del corredor biológico Chichinautzin y la Sierra de Huautla en el estado de Morelos. 8 records from Primer monitoreo en áreas de compensación por pérdida de biodiversidad relacionadas al Gasoducto Mamonal-Paiva. 1 records from Herpetofauna asociada a la cuenca del río Quito - Chocó, 2014. 4 records from Monitoreo de fauna silvestre en el Proyecto Vial 4G Bucaramanga-Barrancabermeja-Yondó (BBY). 431 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN Fase 4 (Anfibios y reptiles). 1 records from Saisies SI Faune - Données naturalistes de Marie BARNEIX. 6 records from Données naturalistes de Pierre DUFRENE. 1 records from Tullie House Museum Natural History Collections. 359 records from Lajitietokeskus/FinBIF - Notebook, general observations. 5 records from 臺東縣轄海岸山脈野生動物重要棲息環境及周遭緩衝區（成功事業區第40林班至45林班） 動物資源調查與監測計畫（1/3）. 197 records from Amphibia and Reptilia (Luomus). 3 records from Biodiversidad asociada a la declaración del Área Protegida en el Pueblo Indígena EPERARA SIAPIDARA, Resguardo Calle Santa Rosa, Timbiquí (Cauca). 6 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 2 records from Données naturalistes de Frédéric CHICHE. 1 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 2 records from Ecosphère_2017_12_18. 2 records from Liste d'espèces animales recensées au cours des activités de l'Organisation pour le Développement Durable et la Biodiversité (ODDB ONG) au Bénin. 304 records from Israel Nature and Parks Authority. 43 records from Colección de anfibios y reptiles, Universidad del Valle (Colección UV-C). 201 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 7 records from Norwich Reptile Study Group Records for 2011. 3 records from DMNS Herp Collection (Arctos). 153 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 24 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 255 records from RNF - Données de l'association Vivarmor Nature. 5 records from Amphibians (Amphibia, Anura and Caudata) and reptiles (Reptilia, Squamata) from the headwaters of Río Guázaro on the Caribbean versant of Veraguas province, western Panama. 566 records from UCM Amphibian and Reptile Collection (Arctos). 6 records from Inventarios de la biodiversidad en el piedemonte subandino de Yopal. 2 records from Étude pluridisciplinaire sur le mont Itoupé du Parc amazonien de Guyane. 4 records from Oregon State University Herpetological Collection. 1 records from Anfibios y Reptiles del Centro Universitario Regional Noreste (UdelaR). 448 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 1 records from Données du/de la naturaliste zeitouni kevin provenant de la base de donnée du SINP Île-de-France CETTIA. 19 records from Habitats Directive Portuguese Report: Species 2013-2018. 4 records from Colección Herpetológica-Museo de Historia Natural Unillanos. 2 records from Wildmeat consumption by Allebone-Webb 2009 at Equatorial Guinea. 4647 records from Amphibiens et Reptiles de France (Enquête 2). 1 records from Inventario de Herpetología Buenos Aires, Tauramena, Casanare. 62 records from Species recordings from the Danish National portal Arter.dk. 1 records from Données naturalistes de EMERIAU Théo. 1 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 2. 398 records from Royal Belgian Institute of Natural Sciences Reptile collection. 120 records from University of Nebraska State Museum Herpetology Collection. 131 records from Anfibios y reptiles del estado de Nuevo León. 92 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 220 records from Données faune, flore et fonge du Conservatoire des espaces naturels du Nord Pas-de-Calais. 4317 records from Reptiles and Amphibians Dataset. 218 records from Leicestershire and Rutland Reptile Records to 2011. 3 records from Monitoreos en áreas de compensación por pérdida de biodiversidad relacionadas al Gasoducto Loop San Mateo. 1 records from Données opportunistes. 13 records from Données Faune de l'Agence des Espaces Verts (AEV) d'Ile de France. 3 records from Winter Bird Census. 93 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 1 records from Yoann_BLANCHON_2017_12_18. 1 records from Natura 2000 Vallée de l'Esch, d'Ansauville à Jézainville. 5 records from Biodiversidad asociada al gasoducto Loop San Mateo-Mamonal. 12 records from Sbp-BioBlitz2017_60years-BiodiversityData. 1 records from Herpetofauna presente del cerro Alto Santa Fe, Guarato, 2019. 45 records from NRW Regional Data: South East Wales Non-sensitive species. 150 records from National Trust Species Records. 3 records from CMC_herpetology_vouchers. 1 records from Inventarios de flora y fauna en bosques de niebla del municipio de Chámeza, Casanare. 2 records from Caracterizacion de Reptiles del Cerro de Chageradó, Frontino- Antioquia). 2 records from Vertebrados de los humedales de La Mojana, Colombia. 1313 records from Reptile Specimens. 4 records from Inventaire de la faune de vertébrés du Parc national du Mercantour. 11 records from RNF - Données du Conservatoire d'espaces naturel Centre. 1 records from Biodiversidad asociada al proyecto Línea de Transmisión de Energía Segundo Circuito San Lorenzo - Calizas a 110 kV, Antioquia. 1 records from Inventario Fauna Vertebrada de la Manchuela Conquense (CUENCA), 2007. Asociación de Desarrollo Integral de la Manchuela Conquense (ADIMAN). 61 records from NRW Regional Data: North Wales. 27 records from Monitoreo de biodiversidad del Valle del Cerrejón. 304 records from CUMV Amphibian and Reptile Collection. 3 records from DIBA-Provincia de Barcelona y Red de Parques Naturales. 17 records from LERN Records. 2007 records from Miscellaneous records held on the Cofnod database. 8 records from iRecord Surveys. 2 records from Transferts SI Faune - Données naturalistes de Marie BARNEIX. 13 records from Bell Museum amphibians and reptiles. 3 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 46 records from UWBM Herpetology Collection (Arctos). 1 records from Artsrike vegkanter i Haugesund. 4 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 17 records from DREAL_PACA_-_N2000_-_Commune_de_l'Argentière-la-Bessée_2017_12_18. 2 records from Données naturalistes de Cyrille DELIRY. 133 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 2249 records from CM Herps Collection. 80 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 2 records from Données naturalistes de Arnaud HORELLOU. 79 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 1 records from Registro Herpetofauna de los Corregimientos de Juanchaco y Ladrilleros, Municipio de Buenaventura (Valle del Cauca) Septiembre de 2016. 6 records from Biodiversity4all Research-Grade Observations. 34 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 25 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 850 records from RAVON (NL) - Network Ecological Monitoring Reptiles. 340 records from Atlas des amphibiens-reptiles du Nord et du Pas-de-Calais (GON). 107 records from UNR Herpetology. 399 records from Angelo State Natural History Collections (ASNHC) Amphibian and reptile specimens (Arctos). 1 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 38 records from Données naturalistes hors Île-de-France saisies dans Cettia-idf. 4 records from Données 2016 de l'Observatoire de la Biodiversité des Forêts. 84 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Herpetológica). 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 42 records from University of Alberta Museum of Zoology Amphibian and Reptile Collection (UAMZ). 5 records from TWIC Biodiversity Field Trip Data (1995-present). 1 records from Caracterización de Fauna para el plan de Etnodesarrollo de Bahía Cupica, Chocó. 19 records from Herpetofauna de la región El Huizache, San Luis Potosí. 1 records from Données naturalistes de GERRIET Olivier. 1 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 2 records from Formación de la colección de referencia de anfibios y reptiles de la Reserva de la Biosfera de Sian Ka'an. 5 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 3 records from Données bibliographique de la base BOMBINA. 43 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 20 records from Argyll Biological Records Dataset. 45 records from Biodiversitätsdatenbank Nationalpark Hohe Tauern. 7 records from Natural Resources Wales Regional Data : Mid-Wales. 42 records from Dorset SSSI Species Records 1952 - 2004 (Natural England). 1 records from Caracterización de Fauna y Flora en ecosistemas de piedemonte, montaña y humedales en el departamento del Casanare. 1 records from Recensement des reptiles 2012/2014 - Atlas de la biodiversité de Bordeaux Métropole. 3 records from E39 Lyngdal - Ålgård. 4 records from Welsh Invertebrate Database (WID). 127 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 2 records from Herpetofauna de los ríos Mondó y Mondocito, municipio de Tadó, Chocó. 2019. 279 records from Paleobiology Database. 66 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica San cristóbal). 6 records from IndOBIS, Indian Ocean Node of OBIS. 4 records from UK Roadkill Records. 49 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 6 records from Caracterización biológica del Monumento Natural Yaxchilán como un elemento fundamental para el diseño de su plan rector de manejo. 3 records from Données du/de la naturaliste Limagne Vincent provenant de la base de donnée du SINP Île-de-France CETTIA. 94 records from Muestreos de fauna silvestre existente en la franja de protección del embalse y áreas de reserva protectora de la Central Hidroeléctrica Sogamoso. 2 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 89 records from Base de données faune - DREAL Centre-Val de Loire. Polygones. 1 records from Données du/de la naturaliste cecchini sébastien provenant de la base de donnée du SINP Île-de-France CETTIA. 48 records from Anfibios y reptiles del estado de Querétaro. 4347 records from Record Pool. 4 records from fauna_do_municipio_de_araraquara-sp. 8 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 13 records from Données du/de la naturaliste Barande Serge provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Inventaire du legs Thénard (Bourgogne). 186 records from DDT05_2017_12_18. 17 records from CCBER Herpetology Collection. 78 records from Herpetile collection NTNU University Museum. 9142 records from Distribución potencial de las especies de anfibios y reptiles en categoría de riesgo de México. 1365 records from Atlas of amphibians and reptiles in Finland. 754 records from naturgucker. 116 records from Chronicle of Nature - Phenology of Reptiles of Sikhote-Alin State Nature Biosphere Reserve Named After K. G. Abramov. 5 records from Données naturalistes de Charlotte PICARD. 7 records from Anfibios y reptiles de la cuenca alta y media del río Bita, Vichada (Colombia). 1 records from Reptiles de un sector del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia Bio- 2017. 1 records from Colección de Zoología Universidad Icesi: Herpetología. 8 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 28 records from museums-hepertology-biodiversity-records. 51 records from BRERC Notable Species records within the last 10 years. 4 records from Biodiversidad asociada al Estudio de Impacto Ambiental para la Modificación del Área de Perforación Exploratoria Medina Occidental. 2 records from Etude faunistique d'une zone humide à Château-Landon - 77. 320 records from Propuesta para la realización de 37 fichas biológicas de las especies de herpetofauna incluidas en la NOM-059 presentes en la Península de Yucatán. 1 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 1497 records from Arizona State University Herpetology Collection. 2 records from Données du naturaliste Serge Gadoum. 79 records from Herpetofauna del Estado de Veracruz. 1 records from Inventaire éclair de Natureparif 2014. 1 records from Données naturalistes de Xavier JAPIOT. 18 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Nurgush. 21 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 33 records from USGS SESC - Big Cypress - Herpetofauna - 2002-2003. 1 records from Anfibios y reptiles en el municipio Medina, Cundinamarca - Proyecto Colombia BIO. 1 records from Coleccion Herpetologica Reptiles LJAMM-CNP. 2 records from Données DREAL Centre-Val de Loire - Faune - 2018. 2 records from Données du naturaliste DUFRENE ERIC provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Anfibios y Reptiles de Caño Cristales, La Macarena, Meta. 3607 records from MVZ Herp Collection (Arctos). 3 records from Fauna presente en el proyecto Minera de Cobre Quebradona, municipio de Jericó. 1 records from Species of plants, fungi and animals from separate territories of Podesinnia. 338 records from MBML-Repteis - Coleção de Répteis. 24 records from Données d'amphibiens et reptiles. 7 records from RNF - LPO Rhône-Alpes. 1 records from Syndicat_Mixte_du_Massif_des_Monges_2017_12_18. 3 records from Données naturalistes de Benoit FONTAINE. 15 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 2058 records from MCP-Repteis - Coleção de Répteis. 32 records from Amphibians and Reptiles census in the Western Siberia (2002 - 2009 years of research). 4 records from Reptiles del cerro Tapartó, Santa Cecilia - Risaralda. 2020. 1 records from Naturschutzgebiet Lüneburger Heide. 1 records from Fauna de Caño Cristales, Sierra de La Macarena, Meta - Colombia. 119 records from Data collected on citizen science web portal www.ornitho.cat. 79 records from Lund Museum of Zoology (MZLU). 6 records from Données naturalistes de Pierre HUGUENY. 1 records from Field workshop on data publishing in Ethnographic and ecological park "Yugra" (Megion, 1-3 July 2019). Biodiversity assessement.. 3 records from Biodiversidad asociada al gasoducto regional Zona Bananera. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2007 - Mammal Survey Estonia. 1 records from Animals of Polissya Nature Reserve. 1 records from Données du Parc Naturel Régional du Gâtinais Français provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Inventario florístico y faunístico del Parque Nacional Barranca del Cupatitzio, Michoacán. 423 records from Records of protected animals species in Ukraine. 360 records from NBIS Records to December 2016. 8 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 621 records from Occurrence of the reptiles in the Volga River basin (Russia). 2 records from Inventaire de la faune réalisé par Jérôme Fouert. 5 records from Données du/de la naturaliste DAVID Patrick provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Herpetos de un Área Degradada por Actividad Minera en la Costa Caucana. 5 records from Colección de reptiles del Museo de Historia Natural de la Universidad de la Amazonia (UAM-R). 35 records from Dr Mary Gillham Archive Project. 207 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Verified data. 482 records from Données ONF faune-flore-fonge. 4 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 1 records from Caracterización ecológica de reptiles presentes en los bosques subxerofíticos de Unguía, Chocó. 1334 records from Formación de una base de datos y elaboración de un atlas de la herpetofauna de México (Anfibiosreptiles). 268 records from Estonian Nature Observations Database. 56 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1167 records from Herpetology Collection - Royal Ontario Museum. 2 records from Kenneth S. Norris Center for Natural History, University of California, Santa Cruz (UCSC) Amphibian and reptile specimens (Arctos). 13 records from Ohio Wesleyan University Reptile Specimens (Arctos). 1 records from Données naturalistes de DELAMARE Ludivine. 4 records from Biodiversidad asociada al gasoducto Loop Mamonal-Paiva. 1 records from A new species of Bothrops (Serpentes: Viperidae: Crotalinae) from Pampas del Heath, southeastern Peru, with comments on the systematics of the Bothrops neuwiedi species group. 1 records from Données de la naturaliste CAILLIERE Christine provenant de la base de donnée du SINP Île-de-France CETTIA. 26 records from Amphibian and Reptile (NSMK-AR). 32 records from RNF - Données du Conservatoire d'espaces naturel Franche-Comté. 85 records from Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée via les portails gérés par la LPO de 2013 à 2017. 22 records from Données de la structure Département 77 provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Données du/de la naturaliste Fontigny Anne provenant de la base de donnée du SINP Île-de-France CETTIA. 26 records from Cowan Tetrapod Collection - Herpetology. 9 records from Parc_Naturel_Régional_du_Verdon_2017_12_18. 7 records from LSUMZ Herps Collection. 4 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 5 records from Realización de fichas de 12 especies de anfibios y 2 de reptiles. 103 records from Données opportunistes amphibiens-reptiles du Nord et du Pas-de-Calais. 31 records from Incidental herptile records 2005-16. 1 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 1 records from Données naturalistes de Philippe GOURDAIN. 7177 records from SDNHM Herpetology Collection. 1629 records from Inventario Español de Especies Terrestres (MAGRAMA). 1 records from Anfibios y reptiles de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 4 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 398 records from RBINS DaRWIN. 34 records from BioGIS - Reptiles - HUJ collections. 1 records from Análisis de Integridad Biológica para el Distrito de Conservación de Suelos Cañón del Río Grande. Convenio CVC- Univalle 108 de 2017. 427 records from Natural History Museum (London) Collection Specimens. 219 records from SER Species-based Surveys. 345 records from Institut Mediterrani d'Estudis Avançats (CSIC-UIB): IMEDEA-PALEOVERT. 5 records from Tetrápodos de Uruguay. 4 records from Données opportunistes faune. 1090 records from The Finnish Nature League's Spring monitoring. 1 records from Census of animal of Benin: Database 1. 1 records from Données du naturaliste Akaren Goudiaby. 2 records from Sheffield and Rotherham Wildlife Trust - Records. 1790 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 4 records from Jordal. 8 records from Inventario y monitoreo de anfibios y mariposas en la Reserva de Calakmul, Campeche. 287 records from Actualización de la base de datos de la colección nacional de anfibios y reptiles (CNAR). 55 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2015. 1 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 2 records from Données 2014 de l'Observatoire de la Biodiversité des Forêts. 3 records from Institut Mediterrani d'estudis Avançats (CSIC-UIB): IMEDEA-VERT. 1 records from Inventarios de flora y fauna en el piedemonte de los municipios Aguazul, Tauramena y Yopal del departamento de Casanare. 7 records from Données du naturaliste Vincent Vignon. 2165 records from UTEP Herpetology (Arctos). 3 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 8 records from A new species of pitviper of the genus Bothrops (Serpentes: Viperidae: Crotalinae) from the Central Andes of South America. 150 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 136 records from Collection Herpetology SMF. 10 records from Inventaire des espèces animales présentes dans les aires protégées et parcs nationaux au Bénin. 1 records from "Biodiversidad en el valle de Cuatro Ciénegas". (Insectos y reptiles). 1 records from CG04_2017_12_18. 2 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 23 records from Données du/de la naturaliste PIQUET Alison provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Données du/de la naturaliste Swift Olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 174 records from UTEP Herpetology Osteology (Arctos). 59 records from Shropshire Ecological Data Network database. 1 records from Données du/de la naturaliste DURAND Bruno provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 2 records from Données du naturaliste PARIS Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 591 records from UCT: Southern African Reptile Conservation Assessment (1910-2009). 3152 records from NIEK_NES. 1 records from Tornoer Teich. 3 records from Cruzando el Caribe - Construyendo la capacidad para el ecoturismo en el Darién y Urabá. 2 records from HBRG P.F. Entwistle Colln and Notebooks Dataset. 36 records from Vertebrados silvestres en zonas indígenas de la reserva de la biósfera Mariposa Monarca: anfibios y reptiles. 1 records from Données du/de la naturaliste Sarouille Romain provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Some notes on fauna of Tal' river within the Kyiv region. 14 records from Diversidad y distribución de la herpetofauna de la Sierra de Jimulco en la Reserva Ecológica Municipal Sierra y Cañon de Jimulco, Torreón, Coahuila. 1 records from MVZ Hildebrand Collection (Arctos). 3 records from New records and an updated checklist of snakes from Son La Province, Vietnam. 1 records from Données du naturaliste Ivan Lisiecki. 30 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México. 580 records from Parc_National_du_Mercantour_2017_12_18. 5 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 204 records from RECORD Reptilia Data. 1 records from Anfibios y reptiles del municipio de Cuetzalan del Progreso, Puebla. 1 records from National Biodiversity Data Bank. Observation records, 1900-2014. 48 records from RNF - Données de la Fédération des Réserves Catalanes. 30 records from Sistematización de las colecciones científicas del Instituto de Historia Natural y Ecología, (IHNE) Chiapas. 9 records from DREAL_PACA_-_N2000_-_Communauté_d'Agglomération_Sophia_Antipolis_2017_12_18. 1 records from Données naturalistes de Delphine MONTAGNE. 64 records from Chronicle of Nature - Phenology of Reptiles of Darwin Nature Biosphere Reserve. 659 records from FHSM Herps Collection. 2 records from Données naturalistes de Loïc SALAUN. 14 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2009. 7 records from Suivi des reptiles en forêt du Madrillet. 5 records from Reptiles Specimens of Akita Prefectural Museum. 22 records from Reptilia collection of the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 11588 records from Observation.org, Nature data from around the World. 7 records from Inventarios de Biodiversidad para Predios de Compra como inversión del 1% por uso del recurso hídrico del Proyecto Hurón 3 de la compañía Equión Energía Limited. 20 records from UWIZM Snakes. 89 records from Vertebrate observation dataset of North and West Africa (CIBIO-Biodeserts). 11 records from Roadkill. 1 records from Fauna y flora de la cuenca media del río Lebrija en Rionegro, Santander. 2 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2007. 4 records from Données de la structure SHF - Société Herpétologique de France provenant de la base de donnée du SINP Île-de-France CETTIA. 80 records from Atlas des amphibiens et reptiles de Martinique. 1 records from Sapo National Park Chimpanzee Survey 2016. 1 records from Données espèces - Expertise IQE 308. 4 records from Données du naturaliste Sylvestre Plancke. 3 records from UCM Vertebrate Observations Collection (Arctos). 4 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 1 records from Anfibios y reptiles de la sierra de Cuatro Venados, Oaxaca, México. 6 records from Fauna and flora of Sumskyi district in Sumy region of Ukraine. 18 records from Laura Steger and Rick Overson Vertebrate Observations. 1 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 4 records from Données naturalistes de SWIFT Olivier. 4 records from Jeu de données convention Eurovia-SPN-2012-2016. 2 records from Suivi des reptiles, insectes et flore de la forêt départementale de Rolleboise 2009. 25 records from RNF - Données de l'association ASTERS. 5 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 7 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 51 records from Données Faune du Parc national des Pyrénées. 2 records from Données de la naturaliste Audrey Garcia. 1 records from BARTH-Environnement_2017_12_18. 3 records from Amphibians and Reptiles in Protected Areas in Ilocos Norte Province, Luzon Island, Northern Philippines. 77 records from Données d'observateurs divers (observateurs transmettant un nombre de données peu élevé) saisies dans Cettia-idf. 19 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 46 records from SANBI: DNA Banking(1987-2011). 1 records from Tejidos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 236 records from Mohonk Preserve Historical Observational Biodiversity Data. 75 records from UiO NHM Herpetile collection. 28 records from Anfibios y reptiles de las regiones Chimalapas (7) y bosque de coníferas y BMM de Veracruz (11). 54 records from National System of Protected Areas in Poland - Animals. 83 records from Colección de Reptiles del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-R). 10 records from USGS SESC - Everglades - Herpetofauna - 2000-2002. 1 records from Línea base general de anfibios y reptiles para el valle medio del Magdalena - VMM. 1 records from Données du naturaliste Ypres marc marie-ange provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Conventions d’étude sur la biodiversité française – Partenariats du Service du patrimoine naturel. 4 records from RNF - Données de la Communauté de Communes de Gevrey Chambertin. 5 records from Anfibios y Reptiles reportados en humedales del departamento de Córdoba. 88 records from SBMNH Vertebrate Zoology. 79 records from Royal Saskatchewan Museum - Herpetology Collection. 1 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 1 records from Rur. 979 records from Biodiversitätsdatenbank Salzburg. 29 records from Données Faune ANEPE Caudalis 2017. 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 5 records from USGS Nonindigenous Aquatic Species database. 1 records from Transferts SI Faune - Données naturalistes opportunistes de Cedric DEVILLEGER. 1 records from Phragma-Thermis/Thessaloniki. 92 records from Census of the threatened species of Benin.. 853 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 4 records from Données naturalistes de Christel PLATEL. 3 records from SDNHM Paleontology Collection. 1 records from Inventaires et sciences participatives de l'ABT de l'Est Cantal. 4 records from Fauna y flora asociada a la Central Hidroeléctrica Playas. 19 records from Habitats Directive Portuguese Report: Species 2007-2012. 1 records from DREAL_PACA_2017_12_18. 1182 records from Inventario de crotálidos en las zonas áridas del noroeste de México. 1 records from Inventario de Anfibios y Reptiles Mámbita. 1 records from Données espèces - Expertise IQE 39. 1 records from Données diverses du Parc naturel régional de Lorraine. 1 records from Bhutan Biodiversity Portal data. 3 records from Montgomeryshire Wildlife Trust records held by BIS. 4 records from Fauna y Flora de Cinaruco - 2014- 2016. 9 records from Données CDPNE 41 - Faune - études financement DREAL 2017. 2886 records from NMNH Extant Specimen Records (USNM, US). 4 records from Bioimages. 3 records from Etude naturaliste des landes et pelouses à Fulchiron, Maisse (91). 1 records from Aquatic animals of the Kamogawa River Basin (Fukuoka, Japan) with the photo images. 2 records from Amphibians and Reptiles of Santa Cruz Tepetotutla, San Felipe Usila, Oaxaca, México. 2 records from Plan de vertebrados de la Patagonia. 2 records from Transferts SI Faune - Données naturalistes opportunistes de Thierry GATELIER. 1 records from Gunma Museum of Natural History, Amphibia and Reptile Specimen. 2 records from Línea base del medio biótico en los bosques para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguablanca -El Morro Yopal. 1 records from Données du/de la naturaliste GUERARD Anthony provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from SysTax - Zoological Collections. 25 records from Parc_Naturel_Régional_du_Queyras_2017_12_18. 8 records from Données de la base Ecosphère. 7 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2007. 2 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 8 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (CROTRA). 5 records from Colección de Zoología General de la Universidad de Pamplona. 22 records from Miscellaneous records held by BIS. 185 records from Leicestershire and Rutland Environmental Records Centre records pre 2000. 3 records from Données du/de la naturaliste mace sebastien provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from New Mexico Museum of Natural History and Science (NMMNHS) Paleontology specimens (Arctos). 66 records from NMNH Material Samples (USNM). 1 records from Line transect censuses of breeding birds. 36 records from Leicestershire and Rutland Environmental Records Centre records 2010-2014. 1 records from Vertebrados terrestres asociados a los rios Napi y San Francisco, departamento del Cauca, 2018. 2 records from Tejidos de individuos colectados en el plan de monitoreo de biodiversidad en el bloque platanillo de la empresa Amerisur y en los bloques Rumiyaco, Venados y Burdyne de la empresa Gran Tierra, Putumayo. 5 records from Norwegian Biodiversity Information Centre - Other datasets. 129 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données saisies entre 01-01-2017 et 31-03-2018. 115 records from Colección de Reptiles. 3 records from Données du naturaliste Larregle Guillaume provenant de la base de donnée du SINP Île-de-France CETTIA. 1541 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 2 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 5 records from Accessing cryptic diversity in Neotropical rattlesnakes (Serpentes: Viperidae: Crotalus) with the description of two new species. 1 records from Données du/de la naturaliste joseph-edouard jean-philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 14 records from Données faune Indre Nature 2016-2017. 1 records from Ty Canol National Nature Reserve (NNR) Species Inventory. 7 records from Diversidad de grupos selectos de flora (Magnoliopsida: Malvales, Sapindales, Fabales, Laurales, Solanales y Caryophyllales) y fauna (Lepidoptera, Diptera, Odonata, Amphibia, Reptilia, Aves y Mammalia) del APFF Boquerón de Tonalá, Oaxaca, México. 2 records from Tejidos colectados en la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 1 records from Données naturalistes d'Olivier ESCUDER. 5 records from Inventaires faune. 19 records from Southeastern Louisiana University Herpetology Collection. 4 records from Caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 9 records from NHMD Herpetology Collection. 4 records from Colección de Tejidos del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-CT). 130 records from National Trust for Scotland Species Records. 1 records from Fauna reptiliana presente en el resguardo indígena de Arquía, municipio de Unguía-Chocó. 2020. 1 records from Données espèces - Expertise IQE 42. 2 records from Data from Defra Family Organisations supplied to Staffordshire Ecological Record. 2 records from Données de la structure Natureparif/ARB Île-de-France provenant de la base de donnée du SINP Île-de-France CETTIA. 142 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 15 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, méxico. 9 records from Reptiles, amphibians and other animals in the areas of Prysyvaska village territorial community (2021). 1 records from Herpetofauna laguna El Tinije. 1 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 2 records from Données diverses Parc naturel régional de Lorraine. 121 records from Isle of Wight Notable Species. 2 records from Données faune ZNIEFF de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS. 7 records from Base associative de la FNE Ain pour les observations de faune-vertébrés. 1 records from Atlas de la Biodiversité de Seine-et-Marne - volet 2. 3 records from Biodiversidad de Herpetos de las Reservas Naturales de la Sociedad Civil del Parque Natural Regional Páramo del Duende, Valle del Cauca, Colombia. 808 records from Reptile distribution within Broadland (2004-2011): based upon field signs and sightings. 44 records from Long term data from the Hanko Bird Observatory (Halias data). 8 records from Inventaire amphibiens reptiles dans la partie béarnaise du Parc National des Pyrénées. 2 records from DREAL_PACA_-_N2000_-_Communauté_urbaine_Nice_Côte_d'Azur_2017_12_18. 30 records from Herpetofauna de las sierras La Candela, Jerez de García Salinas y El Mastrante. 5 records from Données du/de la naturaliste Rossi Stéphane provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Données du/de la naturaliste HAFFNER Patrick provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from DREAL_PACA_-_N2000_-_Communauté_de_Communes_CIANS-VAR_2017_12_18. 1 records from Données de la structure SFO - Société Française d'Odonatologie provenant de la base de donnée du SINP Île-de-France CETTIA. 14 records from AHPAM_2017_12_18. 13 records from Demografía e historia de vida de la lagartija Xenosaurus newmanorum en Xilitla, San Luis Potosí. 2148 records from University of Florida Herpetology. 1 records from Données naturalistes de Pierre NOEL (pnoel). 5 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 13 records from Données de l'Observatoire de la Faune de Bourgogne. 1 records from Données du naturaliste YVERT Florent provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from CAREC Reptiles. 48 records from Estado actual de la distribución de los anfibios y reptiles de la Región de Los Tuxtlas. 100 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 2 records from UAM Herpetology Collection (Arctos). 1 records from Réalisation du DOCOB Basse Vallée du Loing (77). 38 records from MCNH Museum of Cultural and Natural History Reptile Collection. 1 records from Vegetation survey in Vestfold, Norway 2018. 5 records from Biodiversidad asociada al Estudio de Impacto Ambiental para la modificación de la licencia ambiental del campo de producción Rubiales. 2 records from Données de la structure Département 95 provenant de la base de donnée du SINP Île-de-France CETTIA. 8 records from Estudio de Biodiversidad Mina Calenturitas, Temporada de Lluvias. 8 records from Anfibios y Reptiles presentes en el Bloque Platanillo, operado por Amerisur y los bloques Rumiyaco, Venado y Burdyne, operados por Gran Tierra. 5 records from Caracterización biológica en la Serranía de San Lucas 2015. 141 records from Canadian Museum of Nature Amphibian and Reptile Collection. 88 records from RNF - Conservatoire d'espaces naturel Nord-Pas-de-Calais. 3 records from Inventario de Fauna vertebrada de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 4 records from An annotated type catalogue of amphibians and reptiles collected by Nikolay A Zarudny in Iran and Middle Asia. 1360 records from Ditsong National Museum of Natural History Collection: 1805-2008. 3 records from Fauna y Flora asociada al estudio de Impacto Ambiental del Proyecto Parque Eólico Guajira II. 340 records from Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2017.. 1478 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 72 records from Données d'occurrence Espèces issues de la base Natura 2000 : espèces d'intérêt communautaire et autres espèces remarquables renseignées dans les FSD. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences